Treatment of obstructive sleep apnea patients using oral appliances: Our experiences - Miljuš Dušan; Tihaček-Sojić Ljiljana; Milić-Lemić Aleksandra; Anđelković Marko (Vojnosanitetski Pregled)
Background/Aim. Obstructive sleep apnea (OSA) is one of the most prevalent sleep disorders. It is recognized as a serious risk factor for car and workplace accidents due to daytime sleepiness, and factor for coronary heart diseases and stroke. The aim of this study was to examine the effectiveness of oral appliances for mandibular advance in treating mild to moderate OSA. Methods. A total of 15 patients were included in this study, all diagnosed with mild or moderate OSA. Oral appliances were custom made for each patient in protrusive position at 50% of maximum mandibular advancement. The patients were given instructions not to sleep on their backs and avoid alcohol consumption during the study as these are the factors that can contribute to symptoms progression. Results. Complete and partial treatment success was achieve in 14 of the patients. Apnea-hypopnea index values were significantly lower (p < 0.05) at the end of a 6-month observation period compared to those at the treatment beginning. A great improvement in symptoms was observed, with daytime sleepiness index values significantly reduced already within the first month of the treatment. Conclusion. Treatment of obstructive sleep apnea with oral appliances has proven successful. Patients were comfortable using oral appliances and were ready to wear them for prolonged period of time. Use of oral appliances is very common in the world and should not be discarded. They are also very comfortable, practical and affordable comparing to continuous positive airway pressure (CPAP) apparatus, not to mention surgery. Use of oral appliances is safe and very well tolerated, and ought to be offered to patients with OSA.